On purpose : delivering a branded customer experience people love - Smith, Shaun; Milligan, Andy (London ; Philadelphia : Kogan Page, 2015)
"With a constant stream of new communication channels emerging, the real challenge for marketers is not just making sure their brand is present in each space but staying true to their brand purpose. A follow-up to Bold, the best-selling book which looked at what made cutting edge brands stand out, On Purpose, goes one step further and provides practical advice on how to achieve those same results successfully, over multiple channels. Shaun Smith and Andy Milligan provide a framework for success, explaining how to: --Stand Up: be clear about brand purpose and promise --Stand Out: define, design and deliver distinctive customer experiences across multiple channels --Stand Firm: create strong cultures that sustain results They explain and define how to deliver "on purpose" experiences by using a case study, individual thought pieces by experts in the field, and a key action summary at the end of each chapter"--
"Brands growing rapidly have a clear sense of purpose and the value they bring to their customers and employees. On Purpose is a practical guide to executing business purpose successfully by delivering a branded customer experience people love. It presents a framework for success based on being clear about your brand purpose and promise so you can achieve exceptional results through exceptional experiences. It provides the tools for brands to stand out by defining, designing and delivering distinctive, valuable customer experiences across multiple channels. Because purpose is what you do, not what you claim, On Purpose helps you act on your business purpose by showing you how to make your brand stand out. Each chapter illustrates how to succeed in a specific channel by presenting interviews with purpose-driven leaders such as Vernon Hill (Metro Bank), John Forrest (Premier Inn) and Gav Thompson (giffgaff) and case studies of companies including: - Altro - Barclays Bank - Best Western - citizenM - IKEA - Lego - Liberty Global Business Services - London 2012 Olympics - Lush - Nissan - O2 - Timpson - Zappos"--
Machine generated contents note: Introduction -- Part One Stand up -- 01 Purpose-led by insight -- The wrong kind of purpose -- The right kind of purpose -- Insight helps to keep purpose relevant -- How purpose informs building your business -- Gav Thompson - the visionary -- 02 Purposeful leadership -- It takes conviction -- It is more about behaving in a purposeful way than 'doing good' -- Stay true to your purpose as you grow -- Purposeful leaders show the way -- Purposeful leadership is about behaving, not saying -- Part Two Stand out -- 03 Infectious communication -- Marketing should be a verb, not a noun -- Tell a story that people care about -- Bigger is not better -- When infectious communication goes wrong -- How do you engage in infectious communication? -- How to use infectious communication -- 04 Distinctive customer experience -- Fix it or feature it -- Create a multi-sensory experience -- Drive innovation from a deep understanding of what target customers value -- Reinventing your industry -- Don't 'flat line' the customer experience -- Best Western - 'Hotels with personality' -- 05 Continuous innovation -- Constantly innovate in both large and small ways -- Drive innovation from a deep understanding of what target customers value -- Ensure products, services and your people are distinctive and aligned with the brand purpose -- Focus innovation on the things that make you different -- Stand out - a summary -- Part Three Stand firm -- 06 Cult-like culture -- 07 Distinctive employee experience -- Turn your employees into fans -- Hire for DNA not MBA -- Engage and inspire your people to deliver your customer experience 'on purpose' through branded experience training -- Motivation is a poorly understood concept -- Motivating the greatest team on earth -- 08 Experience measurement -- The service profit chain: reloaded -- The employee experience -- 09 Never stand still -- That Berber moment... -- Get started and keep going -- Never stand still -- Nissan -- Altro -- 10 On Purpose profile -- The On Purpose research findings -- Eight practices common to all purpose-led brands -- 11 How to implement - successfully -- The seven deadly sins of CX -- The CX Seven Step Guide: ENGAGE -- The CX Seven Step Guide: INSIGHT -- The CX Seven Step Guide: DEFINE -- The CX Seven Step Guide: DESIGN -- The CX Seven Step Guide: ALIGN -- The CX Seven Step Guide: MEASURE -- The CX Seven Step Guide: INNOVATE -- 12 Putting the principles into action -- Liberty Global Business Services - case study -- Advice for other leaders -- 13 Putting the principles into practice -- Premier Inn - case study -- Advice for other leaders -- On purpose - the keynote presentation -- The workshop leaders -- Acknowledgements -- Index .
Keywords: Customer relations; Relationship marketing; Branding (Marketing); BUSINESS & ECONOMICS / Customer Relations; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Management